Seizures in autoimmune encephalitis—A systematic review and quantitative synthesis. (21st January 2021) - Yeshokumar, Anusha K.; Coughlin, Arielle; Fastman, Jarrett; Psaila, Kendall; Harmon, Michael; Randell, Taylor; Schorr, Emily M.; Han, Helen; Hoang, Hai; Soudant, Celine; Jette, Nathalie
Abstract: Objective: This study aimed to evaluate the proportion of patients with seizures and electroencephalography (EEG) abnormalities in autoimmune encephalitis (AE) and its most common subtypes. Methods: This systematic review followed Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) standards and was registered with the International Prospective Register of Systematic Reviews (PROSPERO). We searched Medline All, Embase, and PsychINFO in Ovid from inception to June 2019 for articles pertaining to AE and seizure. Included studies reported seizure and/or EEG data in cohorts of ≥10 AE patients. Patient demographics, antibody type, seizure incidence, and EEG findings were extracted. Review of studies and data extraction were performed in duplicate. In addition to descriptive analysis, quantitative synthesis stratified by autoantibody subtype was performed with logistic regression and chi‐square analyses. Results: Our search yielded 3856 abstracts: 1616 were selected for full‐text review and 118 studies met eligibility criteria. Of 3722 antibody‐positive AE patients, 2601 (69.9%) had clinical seizures during the course of their illness. Of the 2025 patients with antibody‐positive AE and available EEG data, 1718 (84.8%) had some EEG abnormality (eg, epileptiform discharges, slowing, and so on). Anti‐ N ‐methyl‐d ‐aspartate (NMDA) receptor encephalitis (anti‐NMDARE) was the most commonly reported type of AE (1985/3722, 53.3%). Of the anti‐NMDARE patients with available seizure or EEG data, 71.8% ( n  = 1425/1985) had clinical seizures during their illness, and 89.7% ( n  = 1172/1306) had EEG abnormalities. For all AE patients and in the anti‐NMDARE subpopulation, seizures were more common in younger patients ( p  < .05). Significance: This systematic review provides an estimate of the proportion of AE patients with seizures, confirming the magnitude of seizure burden in this population. Prospective studies are needed to understand population‐based prevalence of seizures, identify factors associated with seizures, and evaluate particular EEG findings as biomarkers of seizures and outcomes in AE.